2022
DOI: 10.1002/ijgo.14435
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal uterine artery Doppler ultrasound during gestational 21–23 weeks associated with pre‐eclampsia

Abstract: Objective To assess whether abnormal uterine artery Doppler ultrasound during weeks 21–23 of pregnancy was associated with an increased risk of pre‐eclampsia. Methods Our retrospective cohort study analyzed uterine artery ultrasound parameters in singleton pregnant women at 21–23 weeks of pregnancy and assessed the association between abnormal ultrasound findings and the risk of pre‐eclampsia. Multivariate logistic regression analysis was conducted to estimate the relative risk between uterine artery ultrasoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Consequently, PubMed displays more than 10,000 research papers regarding screening strategies for preeclampsia. Some studies have focused on preeclampsia prediction using sFlt-1/PlGF ratio values in the first, second or third trimester [23][24][25][26][27][28][29][30][31][32], while other papers have concentrated on uterine Doppler scan as a predictor of HDPs [33][34][35][36][37][38]. Finally, we discovered two articles which focused on preeclampsia screening using a combination of sFlt-1/PlGF ratio with uterine Doppler ultrasound parameters [39,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, PubMed displays more than 10,000 research papers regarding screening strategies for preeclampsia. Some studies have focused on preeclampsia prediction using sFlt-1/PlGF ratio values in the first, second or third trimester [23][24][25][26][27][28][29][30][31][32], while other papers have concentrated on uterine Doppler scan as a predictor of HDPs [33][34][35][36][37][38]. Finally, we discovered two articles which focused on preeclampsia screening using a combination of sFlt-1/PlGF ratio with uterine Doppler ultrasound parameters [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…These RI values are slightly lower than those obtained in our study, where the mean RI value for preeclampsia was 0.68 ± 0.06. A very recent retrospective study conducted by Li [38] discovered that increased bilateral RI (Odds ratio (OR) 2.83) was an effective marker for preeclampsia prediction. Furthermore, every 0.1 increase in the median multiple of mean RI brought a 22% raise in the risk of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent retrospective study, Li et al [ 64 ] assessed whether an abnormal uterine artery Doppler scan at 21–23 weeks of pregnancy increased the risk of pre-eclampsia. The authors reported that markers such as increased unilateral or bilateral PI (OR 2.36, 6.21, respectively) and increased bilateral RI (OR 2.83), unilateral, or bilateral notch (OR 3.66, 5.80, respectively) were effective tools for the prediction of pre-eclampsia.…”
Section: Relevant Data From the Recent Literature Regarding The Value...mentioning
confidence: 99%